Anti-leishmanial and cytotoxic activities of amino acid-triazole hybrids: Synthesis, biological evaluation, molecular docking and in silico physico-chemical properties. Issue 9 (1st May 2017) - Masood, Mir Mohammad; Hasan, Phool; Tabrez, Shams; Ahmad, Md. Bilal; Yadava, Umesh; Daniliuc, Constantin G.; Sonawane, Yogesh A.; Azam, Amir; Rub, Abdur; Abid, Mohammad
Graphical abstract: Surface overlay of compounds 40 (cyancolor) and 53 (yellow color) with Trypanothione reductase. Abstract: According to WHO, leishmaniasis is a major tropical disease, ranking second after malaria. Significant efforts have been therefore invested into finding potent inhibitors for the treatment. In this work, eighteen novel 1, 2, 3-triazoles appended with l -amino acid (Phe/Pro/Trp) tail were synthesized via azide-alkyne click chemistry with moderate to good yield, and evaluated for their anti-leishmanial activity against promastigote form of Leishmania donovani (Dd8 strain). Among all, compounds40, 43, and53 were identified with promising anti-leishmanial activity with IC50 = 88.83 ± 2.93, 96.88 ± 12.88 and 94.45 ± 6.51 μM respectively and displayed no cytotoxicity towards macrophage cells. Moreover, compound43 showed highest selectivity index (SI = 8.05) among all the tested compounds. Supported by docking studies, the lead inhibitors (40, 43 and53 ) showed interactions with key residues in the catalytic site of trypanothione reductase. The results of pharmacokinetic parameters suggest that these selected inhibitors can be carried forward for further structural optimization and pharmacological investigation.